Determinants of improving the financial security of retired women in Malaysia - Zainuddin, Halimatul Nadia; Mohamad, Nor Edi Azhar; V. Rajadurai, R. Jegatheesan; Sapuan, Noraina Mazuin; Sanusi, Nur Azura (Korea Distribution Science Association, 2022)
The perspectives on aging women's financial security during their retirement years are based on their behavior, planning, and decision-making processes during their working years. Elderly women are considered vulnerable and have a longer life expectancy, lower-income, and limited financial understanding compared to males; therefore, drastic steps need to be taken to improve their financial stability and quality of life. The current study sought to determine the most important contributors to retired women's financial health by measuring the value of four factors/variables: capability, opportunity, willingness, and biopsychosocial. This study used a mixed model approach, with qualitative analysis in the first phase involving a focus group discussion session, a pilot analysis, and quantitative analysis for phase two involving the distribution and collection of questionnaires completed by retired women. The surveys were distributed across Malaysia in five distinct zones and yielded 339 usable replies to support the theory. The outcomes of the Multiple Regression Analysis in Malaysia revealed that capability, opportunity, and biopsychosocial factors are significant predictors of retired women's financial security, whereas the willingness indicator lacked statistical significance.